Feto-Maternal Outcome In Pregnancy Complicated By Oligohydramnios: A Prospective Observational Study - Patel, Archana; Chauhan, Savan M.; A. Kaneria, Rushikumar; N. Shah, Mona (Journal of Neonatal Surgery, 2025)
Introduction: Amniotic fluid plays a critical role in fetal development, providing protection, facilitating movement, and supporting respiratory functions. Oligohydramnios, defined as an amniotic fluid index (AFI) ≤5 cm, is associated with increased perinatal risks, including umbilical cord compression and impaired fetal circulation. This study aims to evaluate maternal and fetal outcomes associated with oligohydramnios in a tertiary care setting. Materials and Methodology: A prospective, observational hospital-based study was conducted over 1.5 years in the Obstetrics and Gynecology Department at a tertiary care hospital in Gujarat. A total of 163 pregnant women with singleton pregnancies between 28-42 weeks gestation and intact membranes were enrolled. Detailed demographic, clinical, and ultrasonographic assessments were performed. Maternal parameters such as parity, gestational age, and associated conditions were recorded. Neonatal outcomes, including birth weight, APGAR scores, NICU admissions, and perinatal mortality, were analyzed. Statistical analysis was performed using rates, proportions, and percentages. Results: Most participants (80.98%) were aged 21-30 years, with 50.30% delivering preterm. PIH (22.7%) and idiopathic factors (41.1%) were the most common causes of oligohydramnios. LSCS was performed in 46.62% of cases. NICU admission was required for 69.94% of neonates, primarily due to preterm birth (29.82%) and low birth weight (16.81%). APGAR scores >7 were observed in 92.64% of neonates. Perinatal mortality was 1.59%. Conclusion: Oligohydramnios is significantly associated with increased rates of preterm birth, LSCS, and NICU admissions. Early diagnosis and fetal surveillance are crucial in optimizing perinatal outcomes and reducing neonatal complications.